Kenneth Wilson - Renormalization and QCD - Wegner, Franz (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2014)
Kenneth Wilson had an enormous impact on field theory, in particular on the renormalization group and critical phenomena, and on QCD. I had the great pleasure to work in three fields to which he contributed essentially: Critical phenomena, gauge-invariance in duality and QCD, and flow equations and similarity renormalization.
Gesehen am 03.08.2020